Success Rate of Trabeculectomy in Secondary Glaucoma after Vitrectomy in Kariadi Hospital, Semarang, Central Java - Farah Maulida; Fifin L. Rahmi; Maharani Cahyono (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Objectives: Vitrectomy with intravitreal injections of gas or silicone oil is commonly used to treat vitreoretinal diseases such as rhegmatogenous retinal detachment, tractional retinal detachment, and vitreous hemorrhage. Some of these procedure can lead to short-term elevations in intraocular pressure (IOP) and ultimately long-term glaucomatous damage if not treated in a timely manner. Trabeculectomy is a widely performed filtering surgery used in these cases. This study is aimed to define the success rate of trabeculectomy for surgical treatment of secondary glaucoma after vitrectomy in Kariadi Hospital, Semarang, Central Java. Methods: Retrospective study was conducted in secondary glaucoma after vitrectomy patient who underwent trabeculectomy from November 2014-Januari 2019 in Kariadi Hospital. The secondary data of baseline IOP, 1 week, 2 weeks, 1 month, and 3 months after trabeculectomy is obtained from medical records. Results: 19 eyes from 19 patients had mean preoperative IOP 35,56 ± 8,40 mmHg, 1 week 21,01 ± 13,83 mmHg, 2 weeks 26,09 ± 11,27 mmHg, 1 month 29,97 ± 13,45 mmHg, and 3 months 25,47 ± 13,43 mmHg. There was significant differences of IOP level in 1 week, 2 weeks, 3 months (p<0.05), and not significant in 1 month (p 0,171). Complete success rate of trabeculectomy in 1 month was 10,5% and 3 months 10,5%. Qualified success rate in 1 month was 15,8% and 3 months 42,1%. Failed in 1 month was 73,7% and 3 month 47,4%. Conclusions: Trabeculectomy in secondary glaucoma after vitrectomy has low success rate.